Shear-mediated platelet activation in the free flow II: Evolving mechanobiological mechanisms reveal an identifiable signature of activation and a bi-directional platelet dyscrasia with thrombotic and bleeding features. (23rd June 2021) - Roka-Moiia, Yana; Ammann, Kaitlyn R.; Miller-Gutierrez, Samuel; Sweedo, Alice; Palomares, Daniel; Italiano, Joseph; Sheriff, Jawaad; Bluestein, Danny; Slepian, Marvin J.
Abstract: Shear-mediated platelet activation (SMPA) in the "free flow" is the net result of a range of cell mechanobiological mechanisms. Previously, we outlined three main groups of mechanisms including: 1) mechano-destruction - i.e. additive platelet (membrane) damage; 2) mechano-activation - i.e. activation of shear-sensitive ion channels and pores; and 3) mechano-transduction - i.e. "outside-in" signaling via a range of transducers. Here, we report on recent advances since our original report which describes additional features of SMPA. A clear "signature" of SMPA has been defined, allowing differentiation from biochemically-mediated activation. Notably, SMPA is characterized by mitochondrial dysfunction, platelet membrane eversion, externalization of anionic phospholipids, and increased thrombin generation on the platelet surface. However, SMPA does not lead to integrin αIIbβ3 activation or P-selectin exposure due to platelet degranulation, as is commonly observed in biochemical activation. Rather, downregulation of GPIb, αIIbβ3, and P-selectin surface expression is evident. Furthermore, SMPA is accompanied by a decrease in overall platelet size coupled with a concomitant, progressive increase in microparticle generation. Shear-ejected microparticles are highly enriched in GPIb and αIIbβ3. These observations indicate the enhanced diffusion, migration, or otherwise dispersion of platelet adhesion receptors to membrane zones, which are ultimately shed as receptor-rich PDMPs. The pathophysiological consequence of this progressive shear accumulation phenomenon is an associated dyscrasia of remaining platelets – being both reduced in size and less activatable via biochemical means – a tendency to favor bleeding, while concomitantly shed microparticles are highly prothrombotic and increase the tendency for thrombosis in both local and systemic milieu. These mechanisms and observations offer direct clinical utility in allowing measurement and guidance of the net balance of platelet driven events in patients with implanted cardiovascular therapeutic devices.